A teacher wellbeing TEACHER WELL-BEING AS THE KEY TO SOLVING LEARNING PROBLEMS IN ELEMENTARY SCHOOLS: Analisis mendalam tentang faktor-faktor apa saja yang mendukung kesejahteraan guru di sekolah dasar - Dede Ginanjar; Fitri Sholihah; Elsha Nurmaida Putri; Leli Halimah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Teacher well-being is a fundamental aspect that directly influences the quality of learning and the resolution of various educational problems in elementary schools. Teachers who have good emotional, psychological, social, and professional well-being tend to be able to manage classrooms effectively, build positive interactions with students, and create a conducive learning climate. This study aims to examine the role of teacher well-being as a key in overcoming learning problems in elementary schools, particularly at SDIT Mutiara Cendekia. The study uses a qualitative approach with a case study design. Data were collected through learning observations, in-depth interviews with teachers and principals, and documentation studies. The results show that low teacher well-being, which is influenced by administrative burdens, work pressure, limited preparation time, and minimal institutional support, has an impact on the decline in the quality of classroom management, variation in learning methods, and student engagement. Conversely, teachers with better well-being showed positive emotional regulation, higher pedagogical creativity, and constructive learning interactions. These findings confirm that improving teacher well-being is not only a personal issue but also an important strategy in improving learning effectiveness. Therefore, schools need to develop policies and programs that support teacher well-being in a sustainable manner as the foundation for improving the quality of basic education.